Asymmetry of the identity. Reflections on Kant’s transcendental deduction - Ivashchenko, Ivan (Sententiae, 2013)
The object of the paper is to consider the potential of Kant’s transcendental argument in re-lation to Ernst Tugendhat’s “symmetry argument”. The point of Tugendhat’s argument is the hypothesis that the relevant epistemic use of the first person singular pronoun in the sentence with the structure like “I know that I φ” (where φ stands for various states of mind) makes sense only when someone else can use this sentence by replacing “I φ” with “he φ”, meaning “me” from the first person perspective. Tugendhat calls this basic principle “veritative sym-metry”. Hence, Tugendhat assumes that self-consciousness can be described in terms of ob-ject-knowledge. At this juncture several problems loom large. For one thing, an immediate consequence of such assumption is reification of self-knowledge due to the demand to assign it to some object (state of mind). Also we cannot explain both a meaningful usage of the first-person pronoun and the link between object knowledge and second level (higher-order) self-knowledge, which we have to reach observing some mental states.